"Graphically individualized": visual art and representation in Melvin Tolson's early poetry. Issue 1 (2nd January 2016) - Krammes, Brent
Abstract: This article examines the frequently overlooked poetry of Melvin Tolson to explore how Harlem Renaissance-era poetry contends with visual technological race bias. Building on cultural criticism from bell hooks and Richard Dyer, it looks beyond the Jazz movement to consider how Tolson's engagement with older visual forms provides a more complete picture of the 1920s' and 1930s' cultural moment. In two poetry collections, Tolson turns to visual forms, the chiaroscuro technique in painting and the woodcut print, to emphasize the pervasive nature of racial bias. This article recontextualizes Tolson's work within 1920s' and 1930s' graphic arts culture: Aaron Douglas, Rockwell Kent, and others, to assert a poetics of hybridity between high and low, modern and vernacular, and visual and literary production. Tolson's appeals to visual forms structure subsections of poems to envision innovative collaboration predicated on strong African American artistic achievement and self-assertion through visual–poetic forms like silhouettes, etchings, and pastels. Tolson's manuscripts persist as counter-galleries against stereotypical images of African Americans that overwhelmed more dominant visual forms like photography and painting, and remind us that visualization can resist as well as subjugate.